Transcriptomic changes in the large organs in lethal meningococcal shock are reflected in a porcine shock model - Brusletto, Berit Sletbakk; Hellerud, Bernt Christian; Olstad, Ole Kristoffer; Øvstebø, Reidun; Brandtzaeg, Petter (Frontiers in Cellular and Infection Microbiology, 2022)
Background Fulminant meningococcal sepsis with shock and multiple organ failure is associated with a massive systemic inflammatory response involving solid organs. We have previously established a porcine model of the disease to study pathophysiologic and possible therapeutic strategies. Objective This study examined whether the organ specific gene expression profile in such a large animal model reflects the profile seen in patients with fulminant meningococcal sepsis. Patients and methods Data from gene expression profiles induced in organs from patients (n=5) and the porcine model (n=8) were imported into the Ingenuity pathway analysis (IPA) software for comparison analysis. The number of meningococci in the organs were quantified by real time-PCR. Results The all-over transcriptional activation between different organs revealed a striking concordance between the patients and the pigs regarding the pattern of transcriptional activation and activated pathways. Comparison analysis demonstrated similar pattern of upregulation of genes being associated with a large range of inflammatory biofunctions in the patients and the porcine model. Genes associated with biofunctions such as organismal death, morbidity and mortality were similarly downregulated in the patients and the porcine model. Comparison analysis of main predicted canonical pathways also demonstrated a high degree of similarity regarding up- and downregulation in both groups. Core analysis revealed different top-upstream regulators in the different organs in the patients. In the patients pro-inflammatory regulators were most activated in the lungs. In the other organs up-stream factors that regulate signaling pathways involved in development, growth, repair and homeostasis and triglyceride synthesis were most activated. In the porcine model, the top-upstream regulators were pro-inflammatory in all organs. The difference may reflect the shorter duration of the porcine experiment than the duration of the patient’s infection before death. Conclusion The inflammatory responses measured on the transcriptomic level in organs in patients with fulminant meningococcal sepsis is reproduced in the porcine model of the disease, although some differences may exist regarding the top-upregulated factors in individual organs. Thus, this large animal model reproduces important immunological features of meningococcal sepsis and can be a valuable tool in further investigations of inflammatory aspects and possible treatment options